Engagement with Care, Substance Use, and Adherence to Therapy in HIV/AIDS - Patrice K. Nicholas; Suzanne Willard; Clinton Thompson; Carol Dawson-Rose; Inge B. Corless; Dean J. Wantland; Elizabeth F. Sefcik; Kathleen M. Nokes; Kenn M. Kirksey; Mary Jane Hamilton; William L. Holzemer; Carmen J. Portillo; et al. (AIDS Research and Treatment)
Engagement with care for those living with HIV is aimed at establishing a strong relationship between patients and their health care provider and is often associated with greater adherence to therapy and treatment (Flickinger, Saha, Moore, and Beach, 2013). Substance use behaviors are linked with lower rates of engagement with care and medication adherence (Horvath, Carrico, Simoni, Boyer, Amico, and Petroli, 2013). This study is a secondary data analysis using a cross-sectional design from a larger randomized controlled trial (n=775) that investigated the efficacy of a self-care symptom management manual for participants living with HIV. Participants were recruited from countries of Africa and the US. This study provides evidence that substance use is linked with lower self-reported engagement with care and adherence to therapy. Data on substance use and engagement are presented. Clinical implications of the study address the importance of utilizing health care system and policy factors to improve engagement with care.